2012
DOI: 10.1016/j.ajog.2012.08.023
|View full text |Cite|
|
Sign up to set email alerts
|

Pneumonia and pregnancy outcomes: a nationwide population-based study

Abstract: Women with pneumonia during pregnancy had significantly higher risk of LBW, preterm birth, SGA, low Apgar scores infants, CS, and preeclampsia/eclampsia, compared to unaffected women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
111
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 38 publications
5
111
3
7
Order By: Relevance
“…A study in Hong Kong in 2004 showed that SARS during pregnancy is associated with high incidences of spontaneous miscarriage, preterm delivery, and intrauterine growth restriction [9]. Another study shows that pregnant women with pneumonia have an increased risk of developing low birth weight infants, preterm births, restricted fetal growth, and 5-minute Apgar score < 7 compared to healthy pregnant women [10]. Although there have been no clinical or serological reports of SARS or MERS in neonatal infections in existing studies [9,11], evidence of vertical mother-to-child transmission in other respiratory viruses such as H1N1 and respiratory syncytial virus have been reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Hong Kong in 2004 showed that SARS during pregnancy is associated with high incidences of spontaneous miscarriage, preterm delivery, and intrauterine growth restriction [9]. Another study shows that pregnant women with pneumonia have an increased risk of developing low birth weight infants, preterm births, restricted fetal growth, and 5-minute Apgar score < 7 compared to healthy pregnant women [10]. Although there have been no clinical or serological reports of SARS or MERS in neonatal infections in existing studies [9,11], evidence of vertical mother-to-child transmission in other respiratory viruses such as H1N1 and respiratory syncytial virus have been reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…34 gebede HINI pandemik virüs nedenli pnömoni saptadıkları çalışmada; tüm hastaların MV desteği aldığı, 6 hastanın ise eksitus olduğunu belirtmiş ve pandemik virüsün tedavisinde antiinfluenza ilaçlarının acil olarak kullanılması gerektiğini vurgulamışlardır 10 . Riski gruplarda mevsimsel grip enfeksiyonu tedavisi için oseltamivirin hastanede hazır olması gerektiği, mevsimsel gribe bağlı ( A/H1N1 , A/H3N2 veya B ) virüslerine karşı morbidite ve mortaliteyi azaltacağı bildirilmiştir 11 . Bir kısım yazarlar influenzanın yoğun bakımlarda ARDS'ye kadar giden ciddi pnömonilere sebep olduğu ve bu vakalarında % 0,5 oranında fatal seyrettiğini belirtmişlerdir 12 .…”
Section: Discussionunclassified
“…Pregnant women are prone to respiratory infection, due to alterations in the immune system and mechanical changes involving the chest and abdominal cavities . Pneumonia also increases the risk of adverse pregnancy outcomes, such as low birthweight and preterm birth, compared to unaffected women . However, adenoviral pneumonia in pregnant patients has not been reported before.…”
Section: Introductionmentioning
confidence: 99%